2021
DOI: 10.1186/s12981-021-00367-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and determinants of women’s knowledge on vertical transmission of HIV and AIDS in South Africa

Abstract: Background HIV/AIDS is still one of the major public health concerns globally. It is one of the major contributory causes of deaths among women in the reproductive age (15–49 years) and has resulted in about 14 million orphaned children globally. Knowledge of Mother-to Child transmission is one of the strategies to fight against HIV. This study, therefore, sought to assess the knowledge and determinants of women’s knowledge on vertical transmission of HIV and AIDS in their reproductive age in S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
9
2
Order By: Relevance
“…More than 90, 397 (94.1%) of women were heard about vertical transmission of HIV a`nd nearly three-fourth (73%) of them perceived as it may transmitted during labor. The prevalence of mothers knowledge about vertical transmission of HIV was higher than what was reported in South Africa (91.4%) 19 and in the Northern Ethiopia (84.5%). 14 …”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…More than 90, 397 (94.1%) of women were heard about vertical transmission of HIV a`nd nearly three-fourth (73%) of them perceived as it may transmitted during labor. The prevalence of mothers knowledge about vertical transmission of HIV was higher than what was reported in South Africa (91.4%) 19 and in the Northern Ethiopia (84.5%). 14 …”
Section: Discussioncontrasting
confidence: 63%
“… 23 Another reason might be due to the inter-regional and rural–urban differentials in access to education and resources, including HIV and AIDS education. 19 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, women who lived in rural areas were less likely to have sufficient knowledge on MTCT of HIV compared to those in urban centers in Rwanda. Studies conducted in Tanzania [ 8 ], Ethiopia [ 11 , 14 , 16 ], South Africa [ 39 ] reported that women who lived in urban areas have increased knowledge on MTCT. The observed disparities (rural/urban) may be due to differences in access to and quality of HIV related information and other resources between these settings.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Darteh et al using data from the 2016 South Africa Demographic and Health Survey showed that the prevalence of knowledge of mother to child transmission of HIV during pregnancy, delivery, breastfeeding was 87.0%, 81.1% and 80.3% respectively. [30] Pregnancy intention was measured using a single question rather than a validated measure for unplanned pregnancy. Some known behavioral and clinical factors for predicting HIV positivity, such as sexually transmitted infections, were not included in our models because the primary study did not evaluate them.…”
Section: Strengths and Limitationsmentioning
confidence: 99%